IMPLEMENTASI PEMBELAJARAN IPA TERPADU BERBASIS MODEL NESTED UNTUK MENINGKATKAN RESPON BELAJAR MAHASISWA UNIPDU JOMBANG - Putra, Miftakhul Ilmi S (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2018)
This study was aimed to description the implementation of Science integrated learning with Nested Model to increase student responses in PGMI. Students of 3th semester majoring in PGMI, Unipdu, Jombang, were subjected with the tested learning method. The study was conducted in September-November 2017 with experimental method. Studentsâ?? performance was assesed through cognitive tests, observation, and interviews. Results of this study indicate that Science integrated learning with Nested Model to improve students responses. Student responses to Science integrated learning with Nested Model is positive.